Analisis Pemenuhan Ganti Kerugian Nelayan Akibat dari Kebijakan Ekspor Pasir Laut Melalui Gugatan Perdata - Clivio Rahardjo (Faculty of Law, Maranatha Christian University, 2025)
The issue in this research concerns an analysis of lawsuits filed by fishermen arising from the sea sand export policy, which may result in economic losses to their livelihoods. The purpose of this research is to analyze the legal claims submitted by fishermen against the government regarding the sea sand export policy that negatively affects their economic livelihood. This study employs a normative juridical methodology, utilizing a statutory, methodical, and conceptual approach based on a literature review. The Indonesian government reinstated the sea sand export scheme it had implemented after nearly 20 years. The sea sand export policy is regulated under Government Regulation Number 26 of 2023. This strategy has been largely rejected by the public, especially by environmental activists, due to concerns that it may damage the marine ecosystem. damage to the marine ecosystem will negatively impact the economic conditions of fishermen. This policy is considered to be in conflict with Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia. One of the initiatives taken by fishing communities to protect their economic rights is to take legal action against the government as the policymaker. Based on research, the sea sand export policy can be categorized as an unlawful act (perbuatan melawan hukum). Fishermen may file a civil lawsuit against the government on the basis of unlawful acts related to the sea sand export policy which is detrimental to their economic life.